Dispute Resolution of Marriage Cancellation through Religious Court Decisions in Indonesia - Harahap, Mhd. Yadi (Universitas Islam Sultan Agung, 2022)
The provisions of Article 22 of Law no. 1 of 1974 concerning Marriage that a marriage can be annulled if the parties do not meet the requirements to enter into a marriage. Unlike the case with a marriage that does not fulfill the pillars of marriage, the consequences of the marriage are invalid and null and void, meaning that the marriage is considered to have never existed. In the context of Islamic law there is a typology of types of marriage. First, a marriage is considered valid if the conditions and pillars of marriage are met. Second, if one of the pillars of marriage is not fulfilled then the marriage is considered invalid. Third, if one of the conditions for marriage is not fulfilled, the fasid marriage can be annulled. How is the resolution of the dispute over the annulment of marriage and the legal consequences of the annulment of the marriage. Empirical research methodology is a method used to answer the above questions, using a statutory and case study approach. While the data sources used consist of primary, secondary and tertiary legal materials using qualitative descriptive analysis. There are at least three legal consequences of resolving disputes over marriage cancellations, namely: the position of the child remains as a legitimate child, joint property can be divided if the marriage is based on good faith, and the husband is not obliged to provide a living for his wife during the iddah period.